Two‐Center Prospective, Randomized, Clinical, and Radiographic Study Comparing Osteotome Sinus Floor Elevation with or without Bone Graft and Simultaneous Implant Placement. (28th August 2015) - Marković, Aleksa; Mišić, Tijana; Calvo‐Guirado, José Luís; Delgado‐Ruíz, Rafael Arcesio; Janjić, Bojan; Abboud, Marcus
Abstract: Purpose: To evaluate stability and success rate of hydrophilic nanostructured implants placed via osteotome sinus floor elevation (OSFE) without grafting material or using β‐tricalcium phosphate (β‐TCP), deproteinized bovine bone (DBB), or their combination, and also to assess three‐dimensional volumetric stability of endo‐sinus bone gained in the aforementioned conditions. Materials and Methods: OSFE with simultaneous implant placement (10‐mm long SLActive‐BL ®, Straumann, Basel, Switzerland) was performed. Grafting materials were randomly allocated to implant sites, whereas one site was left without graft. Implant stability was measured by resonance frequency analysis over 6 months. Implant success was evaluated after 2 years of loading. Volume of new endo‐sinus bone was calculated from CBCT images using 3D Slicer ® software. Results: A total of 180 implants were inserted into posterior maxilla of 45 patients with 6.59 ± 0.45 mm of residual bone height, and all remained successful after 2 years. Implant stability steadily increased during healing, without significant difference between groups ( p  = .658). After 2 years, endo‐sinus bone significantly shrank ( p  < .001) in all groups (DBB:66.34%; β‐TCP:61.44%; new bone formed from coagulum: 53.02%; β‐TCP + DBB:33.47%). Conclusions: Endo‐sinus bone gained after OSFE inevitably and significantly shrinks regardless of whether grafting material is applied or not. Grafting material offers no significant advantage to stability nor clinical success of hydrophilic and nanostructured implants placed simultaneously with OSFE.